Oral infectious bacteria in dental plaque and saliva as risk factors in patients with esophageal cancer. Issue 4 (6th November 2020) - Kawasaki, Machiko; Ikeda, Yuichi; Ikeda, Eri; Takahashi, Momoko; Tanaka, Daiki; Nakajima, Yasuaki; Arakawa, Shinichi; Izumi, Yuichi; Miyake, Satoshi
Abstract : Background: High levels of periodontopathic bacteria as well as Streptococcus anginosus were detected in cancer tissue from patients with esophageal cancer. An association between oral infectious bacteria and esophageal cancer has been reported. Methods: Characteristics of the oral microbiota and periodontal conditions were studied as clinicopathologic factors in patients with esophageal cancer. The study included 61 patients with esophageal cancer and 62 matched individuals without any cancers. Samples of subgingival dental plaque and unstimulated saliva were collected to evaluate the prevalence and abundance of the following oral bacteria using a real‐time polymerase chain reaction assay: Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum, Porphyromonas gingivalis, Prevotella intermedia, Tannerella forsythia, Treponema denticola, and S. anginosus . Results: In the cancer group, the prevalence of all bacteria, with the exception of F. nucleatum, in dental plaque; the prevalence of A. actinomycetemcomitans in saliva; the abundance of all bacteria, with the exception of F. nucleatum and P. intermedia, in dental plaque; and the abundance of A. actinomycetemcomitans and S. anginosus in saliva were significantly higher. Furthermore, a logistic regression analysis suggested that the prevalence of T. forsythia and S. anginosus in dental plaque and of A. actinomycetemcomitans in saliva, as well as a drinking habit, were associated with a high risk of esophageal cancer, with a high odds ratio. Conclusions: The current findings have potential implications for the early diagnosis of esophageal cancer. Abstract : A positive relation is reported between esophageal cancer and specific oral bacteria. Among these bacteria, Aggregatibacter actinomycetemcomitans, a bacterium that the authors previously linked to esophageal cancer, may have strong diagnostic potential because of its rarity in the microbiota of patients with periodontal disease and periodontally healthy individuals.